2015
DOI: 10.1051/epjn/e2015-50007-5
|View full text |Cite
|
Sign up to set email alerts
|

Helium behaviour in implanted boron carbide

Abstract: Abstract. When boron carbide is used as a neutron absorber in nuclear power plants, large quantities of helium are produced. To simulate the gas behaviour, helium implantations were carried out in boron carbide. The samples were then annealed up to 1500°C in order to observe the influence of temperature and duration of annealing. The determination of the helium diffusion coefficient was carried out using the 3 He(d,p) 4 He nuclear reaction (NRA method). From the evolution of the width of implanted 3 He helium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The goal was, however, mainly phase stability and not the properties of isolated defects, nor their role in mass transport kinetics. In spite of a number of experimental works devoted to helium bubbles [11,12,13,14,15,16,17,18,19,20,21] and the related question of helium kinetics [20,22,23,24], not much is known on self-diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal was, however, mainly phase stability and not the properties of isolated defects, nor their role in mass transport kinetics. In spite of a number of experimental works devoted to helium bubbles [11,12,13,14,15,16,17,18,19,20,21] and the related question of helium kinetics [20,22,23,24], not much is known on self-diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we focus on the influence of intrinsic vacancies created under irradiation on the diffusion of helium, which is produced by nuclear reactions in boron carbide submitted to a neutron flux. Such a picture can also be simulated by helium implantation [20], possibly coupled with ion irradiation. We investigate the possible mechanisms at the atomic scale by means of first principles calculations in the framework of Density Functional Theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…This stage could however be related to lithium diffusion leading to unit cell reorganization [28]: in this temperature range, X-ray diffraction performed on a non-polished sample has shown extra-lines that could be attributed to lithium borates. But recent results [20] show that this temperature corresponds to a change in the intragranular helium bubbles from flat to more tridimensional.…”
Section: Annealingmentioning
confidence: 95%
“…But it is also worth considering the actual microstructure of the material. Studies in progress [20] have shown that annealing at 1500°C a helium implanted boron carbide sample leads to coalescence of the helium bubbles located into the grain boundaries, then a possible full opening of the latter: the resulting thermal barriers will certainly have strong effect on thermal conductivity despite a small volume change. This also means that the helium bubbles remain in the material up to the highest temperatures here attained: analyzing helium retention rate requires melting the material.…”
Section: Annealingmentioning
confidence: 99%
“…B and C with energy up to a few MeV. Preliminary tests have been performed [20,21] aiming at reproducing the helium to damage ratio together with a significant helium concentration. We have irradiated a high density boron carbide sample with a dual beam on the Jannus-Saclay facility [22]:…”
Section: Applicationmentioning
confidence: 99%